Shakespeare and the Fall of the Roman Republic Selfhood, Stoicism and Civil War - Gray, Patrick (2018)
Explores Shakespeare's representation of the failure of democracy in ancient Rome This book introduces Shakespeare as a historian of ancient Rome alongside figures such as Sallust, Cicero, St Augustine, Machiavelli, Gibbon, Hegel and Nietzsche. It considers Shakespeare's place in the history of concepts of selfhood and reflects on his sympathy for Christianity, in light of his reception of medieval Biblical drama, as well as his allusions to the New Testament. Shakespeare's critique of Romanitas anticipates concerns about secularisation, individualism and liberalism shared by philosophers such as Hannah Arendt, Alasdair MacIntyre, Charles Taylor, Michael Sandel and Patrick Deneen.